Systematic review of definitions and outcome measures for return of bowel function after gastrointestinal surgery. Issue 1 (1st October 2018) - Chapman, S J; Thorpe, G; Vallance, A E; Harji, D P; Lee, M J; Fearnhead, N S
Abstract: Background: Ileus is common after gastrointestinal surgery and has been identified as a research priority. Several issues have limited previous research, including a widely accepted definition and agreed outcome measure. This review is the first stage in the development of a core outcome set for the return of bowel function after gastrointestinal surgery. It aims to characterize the extent of variation in current outcome reporting. Methods: A systematic search of MEDLINE, Embase, CINAHL (Cumulative Index to Nursing and Allied Health Literature) and the Cochrane Library was performed for 1990–2017. RCTs of adults undergoing gastrointestinal surgery, including at least one reported measure relating to return of bowel function, were eligible. Trial registries were searched across the same period for ongoing and completed (but not published) RCTs. Definitions of ileus and outcome measures describing the return of bowel function were extracted. Results: Of 5670 manuscripts screened, 215 (reporting 217 RCTs) were eligible. Most RCTs involved patients undergoing colorectal surgery (161 of 217, 74·2 per cent). A total of 784 outcomes were identified across all published RCTs, comprising 73 measures (clinical: 63, 86 per cent; radiological: 6, 8 per cent; physiological: 4, 5 per cent). The most commonly reported outcome measure was 'time to first passage of flatus' (140 of 217, 64·5 per cent). The outcomes 'ileus' and 'prolonged ileus' were defined infrequently and variably. Conclusion: Outcome reporting for the return of bowel function after gastrointestinal surgery is variable and not fit for purpose. An agreed core outcome set will improve the consistency, reliability and clinical value of future studies. Graphical Abstract: The absence of a widely accepted definition and agreed outcome measure for postoperative gastrointestinal recovery is a challenge. This study demonstrated wide variation in the reporting of outcomes in previous research. An agreed core outcome set will improve the consistency, reliability and clinical value of future studies. Internationally agreed definitions needed